Education Public Expenditure Review in Zambia - World Bank Group (World Bank, Washington, DC, 2016)
The Zambian education system has been well endowed with public resources and enjoyed a strong commitment from the government. This has enabled the education system to make good progress. Public education financing has gradually shifted toward the upper levels of education. The education system continues to face challenges to improve the efficiency and effectiveness of resource use.